Impetus in Fabrication of Biosensors - Jagriti Narang; Nidhi Chauhan; Nitesh Malhotra (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2015)
A biosensor is an element employed for the detection of an analyte by combining a biological component with a physico-chemical detector component. Biological component can be microorganisms, cell receptors, enzymes, antibodies, nucleic acids. The detector works in a physico-chemical way like electrochemical, optical, piezoelectrical, electrochemical or thermal that transforms the signal resulting from the interaction of the analyte with the biological element into another signal that can be easily measured and quantified.